We the living - Rand, Ayn (Signet, 2011)
First published in 1936, this classic novel portrays the impact of the Russian Revolution on three human beings who demand the right to live their own lives and pursue their own happiness. This is not a story of politics, but of the men and women who have to struggle for existence behind the Red banners and slogans.